Application of siderite tailings in water-supply well for As removal: Experiments and field tests. (March 2018) - Wang, Zhiqiang; Ma, Teng; Zhu, Yapeng; Abass, Olusegun K.; Liu, Lin; Su, Chunli; Shan, Huimei
Abstract: Low-grade siderite tailings are difficult to be utilized. For further exploration on the application of siderite tailings for arsenic removal, a series of theoretic and practical studies were carried out. According to the experiment results and technical specifications, a water supply well using composite filtration materials of siderite and river sands was designed and a pilot run was conducted in Datong basin, China, where the groundwater notably contains high concentrations of arsenic. Particle size of 1–2 mm was selected as the optimum scheme considering the adsorption kinetic parameters and technical specifications. Langmuir isotherm yielded a better fit to experimental data with regard to the siderite with a grain size range of 1–2 mm (R 2  = 0.983), which indicated that the process generally tends to be a monolayer adsorption reaction with a saturation adsorption capacity of 0.5233 mg g −1 . Volume proportion coefficients α = 0.5 was selected as the optimal scheme in view of economic factors. The supply water well using composite filtration materials as a pilot run performed well, with average effluent concentration of 247.57 μg L −1, and arsenic removal rates of 52%–65%. The mechanism for arsenic removal is likely due to the hydroxyl group of Fe(OH)x/FeOOH which contributed from the hydrolysis of FeCO3, and subsequently substituted by aqueous arsenic. Moreover, the groundwater chemical environment contains high sulfide concentrations, which enhances the sorption of arsenic. Highlights: A feasible method to reuse siderite tailings is provided for high arsenic groundwater treatment in remote rural areas. Mechanism of arsenic removal by composite filtration materials is identified. Groundwater chemical environment with high sulfide concentrations enhances the arsenic adsorption ability of siderites.